2007
DOI: 10.1080/10236240701393263
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of temperate and sub-tropical reef fishes towards a stationary SCUBA diver

Abstract: Using remote underwater stereo-video systems we examined fish behaviour towards a stationary SCUBA diver at temperate (Rottnest Island) and sub-tropical (Houtman Abrolhos Islands) reefs in Western Australia. Changes in species richness, relative abundance, fish length, and the mean distance of individual fish from stereo-video cameras, in the presence and absence of a SCUBA diver, were assessed to infer changes in behaviour. Results show that a stationary SCUBA diver may obtain accurate measures of species ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 32 publications
1
66
3
Order By: Relevance
“…For example, MacNeil et al (2008a) found that scarids had a relatively low probability of detection despite their physical conspicuousness, and attributed this incongruity to the species' highly mobile nature and diver-averse behaviour. The behaviour of many fishes changes in the presence of divers (Kulbicki 1998, Watson & Harvey 2007, which may explain why some researchers have found BRUV to be especially effective at observing predatory and mobile species, such as elasmobranchs or species that are targeted by fishing , Cappo et al 2004, Watson et al 2005, Watson & Harvey 2007. Other research, however, demonstrates that mobile predators can be accurately surveyed using UVC (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, MacNeil et al (2008a) found that scarids had a relatively low probability of detection despite their physical conspicuousness, and attributed this incongruity to the species' highly mobile nature and diver-averse behaviour. The behaviour of many fishes changes in the presence of divers (Kulbicki 1998, Watson & Harvey 2007, which may explain why some researchers have found BRUV to be especially effective at observing predatory and mobile species, such as elasmobranchs or species that are targeted by fishing , Cappo et al 2004, Watson et al 2005, Watson & Harvey 2007. Other research, however, demonstrates that mobile predators can be accurately surveyed using UVC (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…After deployment, the boat motored away from the area. We deployed 2 BRUV units concurrently at a minimum of 500 m apart to minimize the overlap of bait odour plumes , Harvey et al 2007, Heagney et al 2007). Where BRUV units could not be separated spatially, replicates occurring < 500 m apart were deployed at least 1.5 h apart.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations